Clinical practice of the dental hygienist - Wilkins, Esther M. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2009)
From the Publisher: The cornerstone text of almost every dental hygienists library is now in its thoroughly updated Tenth Edition. Written in a straightforward, concise outline format, this text equips both students and practitioners with the clinical and educational skills needed for successful practice. Features include full-color artwork and photographs, case-based exercises, procedure boxes, and ethics boxes. The Tenth Edition presents the latest technical advances and research findings and includes a new chapter on teeth whitening.
Includes bibliographical references and index.
Keywords: Dental hygiene; Dental Prophylaxis; Dental Hygienists